Crescimento e respostas fisiológicas de Ricciocarpus natans expostas ao cádmio, cobre e níquel em duas temperaturas (25 e 27 ºC) - Cabral, Andresa Lana Thomé Bizzo (2020)
Industrial activities, such as the production of sugar and alcohol by plants, have generated by-products that have high concentrations of metals in their composition, for example, vinasse. Thus, the integrity of ecosystem processes becomes threatened, as they are the main recipients of pollutants / contaminants, with consequences for the associated biota. Metallic elements can be toxic in high concentrations, causing changes in photosynthetic activity and protein damage to plants. Another environmental condition that contributes to altering the integrity of the aquatic ecosystem is the increase in temperature due to global warming. Thus, investigations on growth and physiological responses of aquatic plants subjected to contamination by metals at different concentrations and temperatures are necessary to understand the ability of some species to tolerate varying concentrations of metals and temperature variation. This study evaluated growth and physiological responses of individuals of Ricciocarpus natans exposed to concentrations of Cd (0.001; 0.01 and 0.375 mg / L), Cu (0.002; 0.009 and 0.385 mg / L) and Ni (0.002; 0.025 and 0.221 mg / L) individually and in combinations, under two temperatures. In addition, growth, and physiological responses in R. natans exposed to dilutions of sugar cane vinasse (5%, 10% and 50%) were evaluated under two temperatures. Over 21 days (every seven days) the following parameters were evaluated: growth (biomass and size in width), photosynthetic pigments (chlorophyll a, chlorophyll b and carotenoids), non-enzymatic antioxidants (anthocyanins and flavonoids) enzymatic (superoxide dismutase and catalase), electrolyte leakage and lipid peroxidation (MDA). The growth coefficient and physiological responses of R. natans were affected by exposure to Cd, Cu and Ni, both at 25 ºC and 27 ºC. With only 7 days of exposure, the combinations of metals and dilution of vinasse negatively affected the growth kinetics of R. natans and the physiology, and the experiment was concluded. R. natans exposed to metals in the lowest concentrations (0.001; 0.01 mg / L Cd, 0.002; 0.009 mg / L Cu and 0.002; 0.025 mg / L Ni) showed a reduction in MDA followed by an increase in antioxidants, suggesting activation of the defense the stress to which the plant has been subjected. However, at 27ºC with exposure to metals, there was a greater content of electrolyte leakage in R. natans indicating alteration of the cell membrane. The reduction of photosynthetic pigments under high concentrations of metals (0.375 mg/L Cd, 0.385 mg/L Cu and 0.221 mg/L Ni), collaborates with the reduction of plant growth exposed to metals both individually and in combinations, representing a relationship between the damage caused by oxidative stress. In this study, Ricciocarpus natans showed a detoxification mechanism for Cd, Cu and Ni in low concentrations (0.001; 0.01 mg/L Cd), (0.002; 0.009 mg/L Cu) and (0.002; 0.025 mg/L Ni) through increased antioxidant production and tolerance to variation of 2ºC. Thus, the results of this study contribute to the understanding of the changes that metals, either individually or in combinations, and the increase in temperature, can induce in the growth and physiological parameters of aquatic macrophytes.